(untitled) (Brazilian Journal of Radiation Sciences, 2019)
Belo Horizonte, the capital of Minas Gerais, is one of the largest cities in Brazil. It is geographically centered on a region with intense mining and industrial activity and a fleet of more than 1.5 million vehicles. The numerous sources of atmospheric emissions of particulate matter in this capital and its vicinity offer a considerable risk to the degradation of air quality. In order to contribute with elemental composition of particulate matter, the Nuclear Technology Development Center / Brazilian Commission for Nuclear Energy, and the Department of Nuclear Engineering of the Federal University of Minas Gerais has developed a research based on environmental samples. This work aims to present the sampling methodology, the concentration values of sampled particulate matter preliminarily, the methodology of analysis of elemental concentration using the nuclear technique of neutron activation analysis, k0-standardized method, and interpreted through statistical techniques and values of the elemental concentrations more representative of the samplings carried out. The results pointed out the vehicle emissions as the major source that contributes to airborne particulate matter followed by soil resuspension.